Deeper Learning - How can it revolutionize African education and prepare students for the future workforce? - AMBALIKA DOGRA (The Journal of Quality in Education, 2019)
The term 'Deep learning' is widespread today from the name of machine learning. On the contrary, another term 'Deeper Learning' from the area of education was prevalent a decade ago, but now it is becoming a fashionable phrase for educationists. It is not just a buzz word, but it also has a power to change the status quo of education and revamp it to the next level. Though, it has the potential to transform teaching and learning, it is still unsure how to gear it up in education and perhaps, a stronger and a new pedagogy is much needed here to usher into fourth industrial revolution.